Exploring EFL Teacher's Agency and Self-efficacy in their Professional Practice among Indonesian EFL Teachers - Utami, Artine Ayu; Kuswandono, Paulus (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Studies on language teachers' agency and self-efficacy have shown that both are essential elements of teachers' identities and practices. However, only some researchers have explored how teachers perceive their agency and self-efficacy in the Indonesian context. Thus, this study aimed to investigate how English teachers perceive their agency and self-efficacy in their teaching practices and environments. This study employed a mixed method study in which both quantitative and qualitative data were utilized to answer the inquiry. The results shed light on how teachers perceive agency with school conditions, how they perceive their self-agency, and their aspiration to become agentic teachers. It was revealed that the majority of the teachers perform professional development to stimulate their agency and efficacy. Challenges were also explored in this article. The evidence of this study imparts policy and practice implications as well as future research direction to gain a deeper understanding of teachers’ agency and efficacy as well as to foster the practice in school contexts.